Early Detection and Intervention Practices Provided by Physical and Occupational Therapists in Saudi Arabia for Children with or at Risk for Cerebral Palsy - Gmmash A; Aljuhani T; Albesher RA (Journal of Multidisciplinary Healthcare, 2025)
Afnan Gmmash,1 Turki Aljuhani,2,3 Reem A Albesher4 1Department of Physical Therapy, Faculty of Medical Rehabilitation Sciences, King Abdulaziz University, Jeddah, 22252, Saudi Arabia; 2Department of Occupational Therapy, College of Applied Medical Sciences, King Saud Bin Abdulaziz University for Health Sciences, Riyadh, Saudi Arabia; 3King Abdullah International Medical Research Center, Riyadh, Saudi Arabia; 4Department of Rehabilitation Sciences, College of Health and Rehabilitation Sciences, Princess Nourah Bint Abdulrahman University, Riyadh, 11671, Saudi ArabiaCorrespondence: Afnan Gmmash, Department of Physical Therapy, Faculty of Medical Rehabilitation Sciences, King Abdulaziz University, Jeddah, Saudi Arabia, Tel +966 500310055, Email asgmmsh@kau.edu.saPurpose: Accurate cerebral Palsy (CP) diagnosis is possible before or at the age of 5 months. However, little is known about the practice of early detection guidelines in Saudi Arabia. The objective of this study was to explore the current physical therapy (PT) and occupational therapy (OT) early detection practices for children (0– 3 years) with or at risk for CP and knowledge and application of evidence-based practices (EBP) for these children.Patients and Methods: A cross-sectional study using a purpose-developed electronic survey was distributed to physical and occupational therapists who work with young children with or at risk of CP. Descriptive statistics and cross-tabulations were employed to analyse the data.Results: A total of 76 participants completed the survey questions and were included in the analysis. Less than half of the patients (46%) received a diagnosis of being at risk for CP between 0 and 5 months of age. Only 16% of the participants are certified in using the Prechtl Qualitative Assessment. Seventy-eight percent of the participants provide parents with prognostic information regarding their children’s diagnosis. Sixty-six percent of the providers always used goal-oriented therapy, 30% always used Neurodevelopmental Treatment, 22% always used passive intervention, and 84% always used caregiver education in their treatment. Application of constraint-induced movement therapy was significantly correlated with a number of demographic variables.Conclusion: This study showed that the majority of therapists consider EBP in evaluating and treating young children with CP. However, more attention should be directed toward training therapists to utilize sensitive tools to detect CP early, enabling them to incorporate EBP in their management plan. Although therapists follow some of the recommended interventions, many therapists still use ineffective treatments with children with CP. A national guideline is required to unify practice and illustrate the role of PT and OT in the management of CP.Keywords: pediatric, rehabilitation, infants, cerebral palsy, early diagnosis